2017
DOI: 10.1017/ice.2017.42
|View full text |Cite|
|
Sign up to set email alerts
|

Carbapenem-ResistantEnterobacteriaceae: A Strategic Roadmap for Infection Control

Abstract: The incidence of carbapenem-resistant Enterobacteriaceae (CRE) has increased worldwide with great regional variability. Infections caused by these organisms are associated with crude mortality rates of up to 70%. The spread of CRE in healthcare settings is both an important medical problem and a major global public health threat. All countries are at risk of falling victim to the emergence of CRE; therefore, a preparedness plan is required to avoid the catastrophic natural course of this epidemic. Proactive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 141 publications
(290 reference statements)
0
62
0
1
Order By: Relevance
“…It has been reported that outbreaks due to CRE have been effectively controlled by enhanced environmental disinfection using hydrogen peroxide (326). Particular efforts should be taken to investigate possible environmental reservoirs during outbreaks (327), and if the source is identified, targeted measures are required to control the outbreak. For instance, duodenoscopes have been identified as the contamination source for several outbreaks, which were subsequently controlled by enhanced cleaning and a change from high-level disinfection to gas sterilization (328,329).…”
Section: Ndm Carbapenemasesmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that outbreaks due to CRE have been effectively controlled by enhanced environmental disinfection using hydrogen peroxide (326). Particular efforts should be taken to investigate possible environmental reservoirs during outbreaks (327), and if the source is identified, targeted measures are required to control the outbreak. For instance, duodenoscopes have been identified as the contamination source for several outbreaks, which were subsequently controlled by enhanced cleaning and a change from high-level disinfection to gas sterilization (328,329).…”
Section: Ndm Carbapenemasesmentioning
confidence: 99%
“…The sources of outbreaks may not be identified in many cases. In such cases, the entire environment of affected wards may become heavily contaminated, and temporary ward closures have been recommended for enhanced cleaning and limiting the further spread of the pathogen (327,(331)(332)(333). External audits of infection control measures and extensive health service-wide education have also been recommended (334).…”
Section: Ndm Carbapenemasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies to manage CRE colonized/infected patients and to control outbreaks in health care facilities have been reviewed. [109][110][111] Both the WHO 112 and the CDC 113 provide detailed guidance on methods to control CRE. The use of bundles to control horizontal transmission of CRE in health care facilities have been reviewed.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%